2011
DOI: 10.1638/2010-0139.1
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Parameters of Captive Western Lowland Gorillas (Gorilla gorilla gorilla)

Abstract: A total of 163 echocardiographic studies on western lowland gorillas (Gorilla gorilla gorilla) were submitted for evaluation; 140 from 99 animals were suitable for analysis. Of these, 81 studies (42 studies from 35 males ranging in age from 11-41+ yr and 39 studies from 31 females ranging in age from 11-41+ yr) are reported here. Three studies from 3 females and 56 studies from 30 males were excluded from this report due to cardiac abnormalities. Cardiac parameters measured were aortic root (Ao Rt) diameter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…In gorillas, echocardiography revealed increasing left ventricular wall thickness from 1.6 cm in young adult males to >2.1 cm in males >31 yo, while left ventricular chamber size decreased. 180 In that study, female gorillas showed little difference in cardiac measurements with advancing age, with left ventricular wall thickness ranging from a minimum of 0.9 cm to a maximum of 1.4 cm. All of the males between 31 and 40 yo in the study were considered to have cardiomyopathy.…”
Section: Heart Disease In Apes Compared With Humansmentioning
confidence: 80%
“…In gorillas, echocardiography revealed increasing left ventricular wall thickness from 1.6 cm in young adult males to >2.1 cm in males >31 yo, while left ventricular chamber size decreased. 180 In that study, female gorillas showed little difference in cardiac measurements with advancing age, with left ventricular wall thickness ranging from a minimum of 0.9 cm to a maximum of 1.4 cm. All of the males between 31 and 40 yo in the study were considered to have cardiomyopathy.…”
Section: Heart Disease In Apes Compared With Humansmentioning
confidence: 80%
“…Clinical grade elevation of blood cholesterol is common in captive great apes on a wide range of diets (reviewed in Finch and Stanford, 2004, Table 3A). Although sudden death from heart failure is common in captive great apes, it may arise more frequently from fibrotic cardiomyopathy (Varki et al, 2009; Great Ape Heart Project, 2012) than from ischemic cardiovascular disease (Manning, 1943; Murphy et al, 2011). The relationship of various heart conditions to conditions of captivity is poorly understood.…”
mentioning
confidence: 99%
“…Evidence consistent with this includes a study that showed an association between extraversion and higher rates of affiliation in a subsample of these gorillas [8]. Another possibility is that low extraversion could be linked to cardiovascular disease, which is the primary cause of mortality in captive gorillas [19].…”
Section: Discussionmentioning
confidence: 70%